DOP89 Impact of biologics on the risk of early postoperative complications in Crohn's disease: a French nationwide study. (30th January 2023) - Fumery, M; Nancey, S; Nachury, M; Allez, M; Rouillon, C; Boureille, A; Altwegg, R; Serrero, M; Vuitton, L; Bouguen, G; Abitbol, V; Boualit, M; et al.
Abstract: Background: While the effect of anti-TNFs on postoperative outcomes in patients with Crohn's disease (CD) has been widely studied, the impact of vedolizumab and ustekinumab on the risk of postoperative complications remains poorly known. Methods: All consecutive patients who underwent intestinal resection for CD between July 2014 and April 2022 within 22 French centers were included in a retrospective cohort. The risk of early post-operative complications (≤30days) in patients exposed to biologics was compared to patients not exposed by logistic regression and propensity score-matched analysis adjusted for age, previous intestinal resection, corticosteroids or immunosuppressants exposure, disease activity, presence of abscess, urgent surgery and initial stoma (preoperative contra-indication to anastomosis). Results: Among the 1201 patients included, respectively 491 (41%), 76 (6.3%) and 57 (4.7%) were exposed to anti-TNFs, ustekinumab, or vedolizumab within six months before surgery. A total of 317 (26.4%) patients had at least one complication of which 123 (38%) were considered as severe (DINDO III/IV). New surgery was necessary in 69 (5.7%) patients and secondary stoma in 23 (1.9%). Three deaths were observed (0.25%). The rates of overall complications in patients not exposed to biologics, exposed to anti-TNFs, ustekinumab or vedolizumab were respectively 26.1%, 25.1%, 34.7% and 29.8%. The risks of intra-abdominal infectious complications in these four groups were respectively 13.5%, 11.1%, 13.3% and 8.8%. In multivariate analysis, age [OR, 1.02 (1.01-1.04); p=0.004], disease activity [OR, 8.36 (1.79 – 149); p=0.037], the presence of an abscess [OR, 2.01 (1.25-3.20); p=0.004] and initial stoma [OR, 1.70 (1.10 –2.61); p=0.016] were significantly associated with intra-abdominal infectious complications. Conversely, preoperative enteral nutrition [OR, 0.12 (0.01 -0.59); p=0.040] was associated with a reduction in this risk. Exposure to anti-TNFs [OR, 0.80 (0.51-1.24); p=0.31], ustekinumab [OR, 1.17 (0.39-3.51); p=0.78] and vedolizumab [OR, 1.28 (0.32-5.17); p=0.72] within the 3 months before surgery were not associated with the risk of intra-abdominal infectious complications. Similar results were observed in patients exposed to these treatments in the month before surgery. Conclusion: In this large cohort, a quarter of patients operated on for CD presented an early postoperative complication and 10% a severe complication. Preoperative exposure to anti-TNFs, vedolizumab or ustekinumab was not associated with an increased risk of early postoperative complications. Preoperative enteral nutrition was associated with a reduced risk of intra-abdominal infectious complication.